Implementation of paediatric vision screening in urban and rural areas in Cluj County, Romania - Jan Kik; Mandy Nordmann; Simona Cainap; Mihai Mara; Daniela Rajka; Monica Ghițiu; Alin Vladescu; Frea Sloot; Anna Horwood; Maria Fronius; Cristina Vladutiu; Huibert Jan Simonsz (BMC, 2021)
Abstract Background In 2018 and 2019, paediatric vision screening was implemented in Cluj County, Romania, where universal paediatric vision screening does not yet exist. We report on the preparation and the first year of implementation. Methods Objectives, target population and screening protocol were defined. In cities, children were screened by kindergarten nurses. In rural areas, kindergartens have no nurses and children were screened by family doctors' nurses, initially at the doctors' offices, later also in rural kindergartens. CME-accredited training courses and treatment pathways were organised. Implementation was assessed through on-site observations, interviews, questionnaires and analysis of screening results of referred children. Results Out of 12,795 eligible four- and five-year-old children, 7,876 were screened in 2018. In the cities, kindergarten nurses screened most children without difficulties. In Cluj-Napoca 1.62x the average annual birth rate was screened and in the small cities 1.64x. In the rural areas, however, nurses of family doctors screened only 0.49x the birth rate. In 51 out of 75 rural communes, no screening took place in the first year. Of 118 rural family doctors' nurses, 51 had followed the course and 26 screened children. They screened only 41 children per nurse, on average, as compared to 80 in the small cities and 100 in Cluj-Napoca. Screening at rural kindergartens met with limited success. These are attended by few children because of low population density, parents working abroad or children being kept at home in case of bad weather and road conditions. Conclusions Three times fewer children were screened in rural areas as compared to urban areas. Kindergartens in rural areas are too small to employ nurses and family doctors' nurses do not have easy access to many children and have competing healthcare priorities: there are 1.5x as many family doctors in urban areas as compared to rural areas. For nationwide scaling-up of vision screening, nurses should be enabled to screen a sufficient number of children in rural areas.